The Effect of Education with Digital Leaflets on Increasing Knowledge about Dyslipidemia and its Treatment in Kediri City - Maharani Dwi Pratiwi; Evi Nurul Hidayati; Okky Intan Mawarni (Sean Institute, 2025)
Dyslipidemia is a major risk factor for cardiovascular diseases such as coronary heart disease and stroke. Leaflets are a suitable information delivery medium for providing education to patients. This study used a quasi-experimental design with a one-group pre-test and post-test design. Respondents were given a knowledge questionnaire before the intervention (pre-test), then received education using a digital leaflet, and then were re-measured (post-test) to see any changes in their level of knowledge. Population: Kediri City residents who are at risk or have predisposing factors for dyslipidemia. The results showed a significant increase in knowledge among respondents after receiving education using a digital leaflet. In the pre-test, the average percentage of correct answers was 79.5%. This measurable increase in knowledge proves that digital leaflets are an effective medium for conveying health information. Education using digital leaflets is effective in increasing public knowledge about dyslipidemia and its treatment in Kediri.